Hyposalivation in a 16‐year‐old girl: a case of salivary gland aplasia. (4th February 2014) - Frydrych, AM; Koong, B
Abstract Salivary gland aplasia is a rare condition with only a small number of cases reported worldwide. It is more commonly seen in males and can occur either in isolation or association with other defects or syndromes. It may or may not occur with a hereditary background. Scant literature exists detailing the status of sublingual salivary glands in patients with any form of major salivary gland aplasia. This case report describes the clinical and magnetic resonance imaging presentation of a 16‐year‐old girl with major salivary gland aplasia detailing the status of all six major salivary glands.